(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Doctors and nurses working in emergency departments (EDs) face chronic occupational stress from long working hours, exposure to critical illness, and demanding clinical responsibilities, predisposing them to adverse metabolic outcomes. This study evaluated the effect of a structured dietary modification and exercise intervention on the metabolic profile and perceived stress of ED healthcare professionals. Methods: A quasi-experimental, single-arm, pre-post study was conducted among 37 doctors and nurses (of 40 enrolled) in the Emergency Department of Believers Church Medical College Hospital, Thiruvalla, India, over 61 days. Participants were trained to abstain from refined sugar and processed food, use stairs instead of elevators, perform body-weight strength training, and walk briskly for 10 minutes daily. Weight, body mass index (BMI), random blood sugar (RBS), lipid profile, liver enzymes (SGOT, SGPT), serum cortisol, and Perceived Stress Score (PSS) were recorded at baseline and on day 61. Paired t-test or Wilcoxon signed-rank test was used for pre-post comparisons, and the Mann-Whitney U test for gender- and profession-wise comparisons. Results: Significant reductions were observed in weight (73.08 to 69.08 kg), BMI (27.66 to 26.15 kg/m²), RBS (110.35 to 104.19 mg/dL), LDL, total cholesterol, triglycerides, SGOT, SGPT, serum cortisol (82.59 to 69.32 nmol/L), and PSS (25.59 to 12.05) (all p<0.05). SGOT and SGPT improved significantly more in males than females (p=0.018 and p=0.007, respectively); no other parameter differed significantly by gender or profession. Conclusion: A short, structured dietary and exercise intervention significantly improved metabolic parameters and reduced perceived stress among emergency medicine doctors and nurses, supporting the feasibility of workplace-based lifestyle interventions for this high-stress workforce.